Non-nominative Subjects: Volume 2 - Bhaskararao, Peri; Subbarao, Karumuri Venkata (Typological Studies in Language, 2004)
Volume 2 of Non-nominative Subjects (NNSs) presents the most recent research on this topic from a wide range of languages from diverse language families of the world, with ample data and in-depth analysis. A significant feature of these volumes is that authors with different theoretical perspectives study the intricate questions raised by these constructions. Some of the central issues include the subject properties of noun phrases with ergative, dative, accusative and genitive case, case assignment and checking, anaphor-antecedent coreference, the nature of predicates with NNSs, whether they are volitional or non-volitional, possibilities of control coreference and agreement phenomena. These analyses have significant implications for theories of syntax and verbal semantics, first language acquisition of NNSs, convergence of case marking patterns in language contact situations, and the nature of syntactic change.